Provision of Urea Fertilizer and Organic Fertilizer of Rice Husk Charcoal on the Growth of Oil Palm Seeds - FS, Harahap; Arman, Iman; Harahap, Nurliana; Fauzi Ahmad, Syawaluddin (Talenta Publisher, 2022)
Good seed growth is a factor in the success of oil palm cultivation due to genetic pre-nursery factors in the field, so that the provision of nutrients in the initial seed growth plays an important role in determining the overall appearance of the seedlings during its growing period. This study aims to determine the effect of oil palm seed growth by applying Uera fertilizer and rice husk charcoal organic fertilizer during the pre-nursery in the field. The experiment was carried out from October 2020 to May 2021 in the experimental garden of the Faculty of Science and Technology, Labuhanbatu University, Rantauprapat at an altitude of 13 meters above sea level. The experimental design in this study was a randomized block design with a factorial pattern that was repeated three times. The first factor is the dose of Uera fertilizer which consists of four levels, namely U0 = 0 kg / ha, U1 = 100 kg / ha, U2 = 200 kg / ha, U3 = 300 kg / ha and the second factor includes the dose of Rice Husk Charcoal Organic Fertilizer (ton / ha) consists of three levels, namely A0 = 0 ton / ha, A1 = 100 ton / ha, and A2 = 200 ton / ha. The results of the experiment showed that there was an interaction effect of uera fertilizer and rice husk charcoal organic fertilizer on plant height (cm),leaf area of ​​oil palm seedlings (cm2), in the number of leaves (leaf) and accretion hump diameter (mm). Treatment of urea fertilizer of 300 kg / ha and organic fertilizer of rice husk charcoal as much as 20 tons / ha produced plant height and leaf area during the pre-nursery